The Role of Geopolitical Components in Afghanistan's National Power - Fayaz Gul Mazloum Yar; Ihsan Ullah Ihsan (RIRAI Publisher, 2024)
This study explores the complex link between geopolitical variables and Afghanistan's power as a nation, providing an important context for understanding Afghanistan's place in the world. The importance of national unity is shown by our findings since 96% of respondents agree that it is important. This highlights the Afghan people's historical fortitude in the face of outside pressures and internal strife.The analysis highlights several other significant geopolitical factors in addition to national unity, such as leadership, Aryan culture, human resources, and geographic position. Together, these elements plus Afghanistan's historical, cultural, and physical background shape the country's might. Notably, despite their historical significance, religion, and natural resources were seen as having less of an impact, defying accepted beliefs about their influence. The study also emphasizes how Afghanistan's national power is dynamic, with new geopolitical components like